Menelisik Perilaku Fraud pada Organisasi Mahasiswa - Hamidah, Empi Wanda; Eryandra, Alvin; Widiasih, Puti Archianti (Jurnal Manajemen, 2024)
This research aims to analyze the factors that cause fraudulent behavior in student organizations. Using a qualitative research approach with phenomenological methods. Data collection techniques include observation methods and in-depth interviews. Therefore, this research makes it possible to obtain broader information and is based on the experience of the sources regarding how and why fraudulent behavior occurs within the scope of student organizations. The characteristics of the resource persons have been determined, namely students who have experience in managing student financial organizations. The resource persons in this research were three students with different organizational backgrounds, and each resource person had experience as a policy maker, directly managing and supervising the finances of their respective organizations. The results of the research show that there is a condition (fraud) in student organizations, in the form of damage to organizational assets and manipulation of the presentation of financial reports. The factors that encouraged this incident to occur were situational pressure, the opportunity to commit the incident (fraud), the action of the incident which was entrenched and considered normal and permitted and the ability of the students who carried out the incident to identify the situation and determine decisions within the organization.